Media Sosial Sebagai Ruang Pembentukan Identitas Diri: Perspektif Al-Qur’an dan Hadist - Muhammad Nugraha Syawalludin; Nurry Fitria; Muhammad Alza Fauzan; Dea Puspita; Asep Sofyan Rahmad; Ismail Mubarok (International Forum of Researchers and Lecturers, 2026)
Social media has evolved from a mere communication tool into a dominant new public sphere for constructing, testing, and asserting modern human identity. On one hand, visual-based digital ecosystems like Instagram offer a platform of freedom for individuals to express their values and life principles. On the other hand, the phenomenon of impression management to pursue social validation often triggers an authenticity crisis and psychosocial pressure due to cyber-social comparison. This study aims to dissect the role of social media as a space for identity formation through the normative lens of Islam, employing a descriptive qualitative method with a library research approach. The results indicate that the Qur'an and Hadith provide a firm moral anchor for a Muslim's digital existence by integrating communication ethics concepts (qaulan sadida and qaulan layyina) and the principle of honesty (ash-shidiq). This research concludes that the ideal virtual identity construction from an Islamic perspective is not a manipulated, superficial persona for popularity, but an authentic digital representation that brings public benefit and remains submissive to Sharia boundaries.